Sexual and Reproductive Health Information-Seeking Behaviour of Undergraduate Students at Mzumbe University, Morogoro €“ Tanzania - Kachota, Beth J.; Kassim, Mohamed (University of Dar es Salaam Library Journal, 2021)
This study investigated the sexual and reproductive health information-seeking behaviour of students in higher learning institutions with specific reference to Mzumbe University. The study sought to answer two questions: first, what are the sources of sexual and reproductive health information used by the students at Mzumbe University; and second, what are the factors affecting the sexual and reproductive health information-seeking behaviour of the students at Mzumbe University. Explanatory research design with both quantitative and qualitative approaches was employed in this study. Findings reveal that students prefer to use social media platforms, consult their peers, and the Internet to meet their various sexual and reproductive health information. Preferences for these sources are associated with, among other things, the freedom they offer to the students when interacting with them for various sexual and reproductive health information. Factors such as traditional values and norms, a sense of embarrassment, availability of online health information, and students ' selected socio-demographic characteristics like age, religion, and marital status were also found to affect the sexual and reproductive health information-seeking behaviour of the students. The study concludes that since the students prefer to use social media, the Internet, and their peers for various sexual and reproductive health information, it is important that they are provided with health information literacy training to help them be able to evaluate the health information obtained from these sources. This is important because it is not clear whether the students get reliable health information from these sources.